Moda e literatura: a poética do vestuário em Macedo e Alencar - Chociay, Lucianne [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This dissertation is an analysis of the descriptions of the clothing worn by the characters and its role in the plot of narratives by Joaquim Manuel de Macedo (1820-1882) and José de Alencar (1829-1877). It is found that, in certain works by Macedo and Alencar, the narrator stresses this aspect and utilizes the different styles of dress of the characters as functional elements in the plot. Fashion and clothing not only represent the social status of the characters, but also, in many cases, character traits, mood, sensuality, behaviour in drawing rooms, etc. In the 19th century, English fashion dominated the male clothing market and Paris was the great radiating centre of female fashion. Novelties arrived in Brazil shortly after being launched, and competed with colonial clothing customs. In Brazilian society and novels of the 1800s the force of colonial tradition was predominant in private life: house-wear was lighter and more appropriate for the tropical climate. French fashion became the rule in the public sphere, in elegant party clothes. With social change fashion became more and more accessible to a greater number of people, and its influence expanded out into other areas. During the 19th century, it became the object of reflection of artists, intellectuals, writers and painters, who perceived its influence on social life. It was in this period that the first theories about fashion arose, influenced by sociology, economics, philosophy and history. These reflections defined various meanings for fashion, the importance of individualism, of novelty and change - the break with tradition - as the principal aspects of the emergence of fashion. Medical texts were couched in a discourse which defended reforms in clothing and condemned certain fashionable items on health grounds. Etiquette manuals sought to regulate dress and promoted a certain conformity to social status. Travel writing by foreign...

O objetivo da dissertação é analisar as descrições do vestuário das personagens e seu papel no enredo de narrativas de Joaquim Manuel de Macedo (1820-1882) e José de Alencar (1829- 1877). Verifica-se que, em algumas obras de Macedo e Alencar, o narrador reforça esse aspecto e utiliza as diferentes maneiras de vestir das personagens como elementos funcionais no enredo. A moda e o vestuário representam não apenas o status social das personagens, mas, em muitos casos, traços de personalidade, estado de espírito, sensualidade, comportamento nos salões, etc. No século XIX, a moda inglesa dominava o mercado do vestuário masculino e Paris era o grande centro irradiador da moda feminina. As novidades chegavam ao Brasil, quase simultaneamente ao lançamento, e passaram a concorrer com os hábitos indumentários coloniais. Na sociedade e no romance brasileiro oitocentista a força da tradição colonial prevalece na vida privada: o vestuário de ficar em casa era mais leve e adequado ao clima tropical. A moda francesa torna-se a regra no espaço público, no vestuário elegante das festas. Com as transformações sociais, a moda, cada vez mais, torna-se acessível a um número maior de pessoas e sua influência se expande para outras áreas. Durante o século XIX, torna-se tema de reflexão de artistas, intelectuais, escritores e pintores, que percebem sua influência na vida social. Neste período surgem as primeiras teorias sobre a moda, influenciadas pela sociologia, economia, filosofia e história. Estas reflexões definiram diversas significações da moda, a importância do individualismo, da novidade e da mudança - o rompimento com a tradição - como principais aspectos da emergência da moda. As obras médicas apresentavam um discurso reformador do vestuário e condenavam alguns itens da moda porque fariam mal à saúde. Os manuais de etiqueta pretendiam regulamentá-lo e promoviam certa...
Keywords: Literatura brasileira; Análise do discurso narrativo; Moda na literatura; Macedo, Joaquim Manuel de